Direct and residual effect of various vermicompost on soil nutrient and nutrient uptake dynamics and productivity of four mustard Pak-Coi (Brassica rapa L.) sequences in organic farming system - N. Nurhidayati; Masyhuri Machfudz; Indiyah Murwani (International Journal of Recycling of Organic Waste in Agriculture)
Abstract Purpose To study the direct effect on the first mustard cropping and the residual effect of three kinds of vermicompost on the productivity of the second, third, fourth Pak-Coi mustard sequential cropping. Method A field experiment was conducted for four sequential planting periods of mustard Pak-Coi in silty clay Inceptisol. The experiment used a factorial randomized block design with two factors. Factor I comprised three kinds of vermicompost with three types of bedding materials; V1—spent mushroom waste, V2—coconut husk, and V3—sugarcane trash, while factor II comprised four different application rates: 5, 10, 15, and 20 t ha−1. From these two factors, there were 12 treatments plus one control treatment (without vermicompost application). Results Application of vermicompost increased soil NPK content. The highest nutrient uptake was also found in the residual effect for the second cropping. Nutrient uptake of the third and fourth mustard cropping had a decreasing trend. The highest yield on the first cropping was found in the application of vermicompost V2 and V1 with the application rates of 10–15 t ha−1. In the second cropping, the productivity increased, whereas the third and fourth sequential cropping decreased in the vermicompost V1 and V2, whereas in the vermicompost V3 the productivity of the third and fourth cropping was slightly increased. Conclusion The application of vermicompost to organic farming provides nutrient availability in four mustard subsequent planting periods. Differences in the dynamics of nutrient availability, nutrient uptake and crop yields are affected by the vermicompost materials used.